The prognostic value of the ESC quality indicators in patients with acute myocardial infarction: a systematic review. (14th October 2021) - Perello-Bordoy, A; Masso-Van Roessel, A; Mas-Llado, C; Ramis-Barcelo, M F; Vives-Borras, M; Pons, J; Peral, V; Rossello, X
Abstract: Background: Quality indicators (QIs) provide a mechanism for measuring opportunities to improve cardiovascular care and outcomes. To help improving quality of care in patients with acute myocardial infarction (AMI), the European Society of Cardiology (ESC) set 20 QIs to evaluate several dimensions of care. These 20 QIs are organized in 3 areas and 7 domain defined in structural, performance measures including patient's feedback and outcomes. Several registries have reported their performance using real-world data, and some of them reported their prognostic value. For this purpose, we systematically reviewed the literature evaluating the 2017 ESC ACVC set of QIs in previous observational studies, with the aim to summarise their prognostic value. Methods: A systematic review of PubMed and Web of Science was conducted including all original articles reporting the use of the ESC QIs in AMI patients. Inclusion criteria were studies providing original data, and studies evaluating the 2017 ESC ACVC set of QIs in patients with AMI (STEMI or NSTEMI). The main exclusion criterion was for non-original articles and studies evaluating a different set of QIs. Adjusted estimates (odds or hazard ratio) for the association between QIs and mortality were used to report the prognostic value of QIs. Results: Among de 220 screened citations, 9 studies met the inclusion criteria after full-text review. Among these 9 studies, there were 11 different cohorts. Patients were recruited from 3 different continents (31 countries) between 2003 and 2018. The association between QIs and mortality have been reported in three cohorts: EPICOR, FAST-MI and MINAP. EPICOR evaluated this association for 15 QIs and 2-year mortality, whereas FAST-MI evaluated the relationship for 11 QIs and 30-day mortality, and MINAP for 9 QIs and 3-year mortality. In general, higher compliance was associated with better prognosis in most QIs (Figure 1). The association between mortality and some QIs (1.3, 3.1, 3.2, and QI 6) was not reported in any study, and their prognostic value is therefore unknown to date. Composite QIs, which combine individual indicators from domains 1–6 to summarise the multiple dimensions of quality of care, were associated with mortality in all comparisons (7.1 was tested in the 3 studies, whereas 7.2 was only tested in EPICOR). Conclusions: Our review has shown a consistent association between higher attainment of QIs and decreased mortality in the three cohorts that evaluated this association. These data support the use of QIs as a useful tool for assessing quality of care across centres and countries. There is a need to design registries and surveys specifically assessing QIs to have a more accurate picture about the implementation of ESC QIs. Funding Acknowledgement: Type of funding sources: None.